Strategi Bauran Pemasaran Pelayanan Kesehatan RSGM XYZ di Era Pandemi Covid-19 - Febriana Kusuma Dian Mayasari (Jurnal Medika Hutama, 2022)
Corona Virus Disease 2019 (Covid-19), which is a global pandemic, affects the health system, including hospital health services in Indonesia. Dental and Oral Hospital (RSGM) which is a special dental and oral health facility must also prepare itself so that the hospital can survive and can provide safe and quality services. One of them is by doing the right marketing strategy. The purpose of this study was to describe the marketing mix strategy of RSGM XYZ during the Covid-19 pandemic, which is related to product, price, place and promotion. This research is a cross sectional study using a qualitative approach. Data collection was carried out by observation, review of internal documents and study of literature. Data collection was also carried out by in-depth interviews with selected informants based on purposive sampling. The results obtained from this study are an overview of the RSGM XYZ marketing mix strategy related to products, prices, places and promotions that have been carried out by the hospital in the face of the Covid-19 pandemic.